Pharmacotherapeutic Profile at a Center for Psychosocial Care Alcohol and Drugs (CAPS-ad) of Northeast Brazil - Ferreira, Alice de Sá; Sodré, Malene Lima Gomes; Cristina Ferreira, Mirlley Cristina Ferreira; Marinho, Suanne Ferreira; Fernandes, Mauricio Avelar; Rodrigues, Márcia de Souza; Belfort, Ilka Kassandra Pereira; Monteiro, Sally Cristina Moutinho (HSJ, 2020)
Objective: To verify the pharmacotherapeutic profile of users of a Psychosocial Care Center for Alcohol and Drugs in Drugs (CAPS-ad) in a capital city in northeastern Brazil. Methods: Exploratory, descriptive, retrospective study with a quantitative approach, performed on drug users over 18 years old, regardless of gender and ethnicity. Data (medications, clinical diagnosis, use of illicit drugs, among others) were collected from the institution's medical records. The analysis was conducted using descriptive statistics (absolute and relative frequencies, mean and standard deviation). Results: 60 medical records of patients being monitored at the CAPS-ad were analyzed, 83.3% of whom were male, with a predominance of patients aged between 30 and 39 years (35%), incomplete primary education (40%) and diagnosis ICD-10 F19 (mental and behavioral disorders due to the use of multiple drugs and the use of other psychoactive substances; 45%). The most prescribed drug class was benzodiazepines (23.8%), with the predominant use of the active component clonazepam (15.4%), followed by antidepressants (16.1%), with amitriptyline (4.9%) being the most prescribed when compared to others in the same class. Conclusion: The study highlighted the importance of the pharmacist's role with the health team to promote the rational use of medicines and the control of adverse reactions and success in drug therapy.